Structural Competency: A Framework for Racial Justice Intervention in Student Affairs Preparation and Practice - Kenyon Lee Whitman; Uma Mazyck Jayakumar (Education Sciences, 2023)
Higher education practices and policies are rooted in racism and imperialism. This causes physical and emotional harm to BIPOC students. Yet, student affairs practitioners and higher education leaders struggle to stay conscious of the relationships between macro structures of oppression and their deleterious educational, economic, health, and social consequences, when it comes time to assess, understand, and intervene in campus crises and racialized violence. Borrowing from the medical field, this paper offers “structural competency” as a framework for student affairs education and practice toward supporting practitioners prepared to mitigate systemic racism and to identify the social determinants of inequity. Structural competency in student affairs means having the capacity to understand and take actions toward addressing the root causes of BIPOC students’ marginalization in historically white campus contexts. It requires deep attention to how these causes—polices, institutional norms, infrastructures, and the hegemonic beliefs embedded in our economic, social, and political systems—interact with students’ lived experiences on campus. Guided by a Critical Race Theory lens, structural competency moves us toward confronting the downstream consequences of upstream decisions such as admissions standards that disenfranchise BIPOC students, or how the federal financial aid formula fails to account for equity in home ownership which disproportionately harms Black families for the benefit of white ones, because of antiblack U.S. policies such as redlining, making college less accessible for BIPOC students. This paper argues that such a structural competency framework and mindset in policy and practice is crucial for higher education leaders confronting systemic institutional policies that have a cumulative and ongoing oppressive impact on BIPOC students.